A companion to Donald Davidson - LePore, Ernest, 1950- (Chichester, West Sussex : Wiley Blackwell, 2013)
A Companion to Donald Davidson presents newly commissioned essays by leading figures within contemporary philosophy. Taken together, they provide a comprehensive overview of Davidson's work across its full range, and an assessment of his many contributions to philosophy. Highlights the breadth of Davidson's work across philosophyDemonstrates the continuing influence his work has on the philosophical communityIncludes newly commissioned contributions from leading figures in contemporary philosophyProvides an in-depth exposition and analysis of Dav.
Includes index.
Includes bibliographical references index.
Print version record and CIP data provided by publisher.
Keywords: Davidson, Donald, -- 1917-2003.; Davidson, Donald, -- 1917-2003.; Davidson, Donald, -- 1917-2003; PHILOSOPHY -- History & Surveys -- Modern; Electronic books; Electronic books